Design elements and principles - Davis, John (New South Wales : Classroom Video, 1989)
Looks at design elements (line, form, light & colour) and principles (scale, diversity, proportion, balance and order)
Writer, Stewart Arden
Presenter: Stewart Arden
VCD format
Keywords: Visual perception; Graphic arts -- Technique; Design